2021
DOI: 10.3390/rs13224572
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Automated Semantic Segmentation of Arctic Shorelines Using Very High-Resolution Airborne Imagery, Spectral Indices and Weakly Supervised Machine Learning Approaches

Abstract: Precise coastal shoreline mapping is essential for monitoring changes in erosion rates, surface hydrology, and ecosystem structure and function. Monitoring water bodies in the Arctic National Wildlife Refuge (ANWR) is of high importance, especially considering the potential for oil and natural gas exploration in the region. In this work, we propose a modified variant of the Deep Neural Network based U-Net Architecture for the automated mapping of 4 Band Orthorectified NOAA Airborne Imagery using sparsely label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…The application of automatic coastal delineation algorithms using remote sensing imagery is usually based on the detection of the waterline through spectral indices, pixel segmentation or and various classification techniques, with recent examples being CoastSat, Waterdetect or XGBoost (Vos et al, 2019;Aryal et al, 2021;Cordeiro et al, 2021). Our comparative analysis has shown that the shoreline changes and volume transfer estimates can be very different depending on the shoreline proxy used -backshore vs. foreshore.…”
Section: Impacts Of Proxy Usagementioning
confidence: 99%
“…The application of automatic coastal delineation algorithms using remote sensing imagery is usually based on the detection of the waterline through spectral indices, pixel segmentation or and various classification techniques, with recent examples being CoastSat, Waterdetect or XGBoost (Vos et al, 2019;Aryal et al, 2021;Cordeiro et al, 2021). Our comparative analysis has shown that the shoreline changes and volume transfer estimates can be very different depending on the shoreline proxy used -backshore vs. foreshore.…”
Section: Impacts Of Proxy Usagementioning
confidence: 99%
“…Although LEUCOTEA allowed to assess some parameters of the energetic balance on the coasts, further studies are needed to integrate the deep learning techniques with other architectures to assess the mass balance [16,91,107]. The assessment of mass balance requires the implementation of different machine learning models, which could involve classification and segmentation techniques for the quantitative evaluation of coastal landforms and sediment typologies [108,109]. For the energetic balance, a full framework of all components must be realized through a joint assessment of current, tide, wave, and wind parameters.…”
Section: Further Developmentsmentioning
confidence: 99%
“…The scale parameter is used to control average image object size [41,42] where a higher value results in bigger objects and a smaller value results in smaller objects. The scale parameter has been considered the primary factor for segmentation in object-based research [43,44] and the determination of the scale parameter depends on factors such as the sensor type, resolution, the purpose of the segmentation, and objects of interest. As a result, we incremented our scale parameter by 100 between 100 and 800 in our threshold-based and supervised classifications to better understand the influence of object size on accuracy.…”
Section: Classification Approachesmentioning
confidence: 99%
“…Object-based and deep learning applications have been applied to infrastructure detection in the Arctic [32], ice-wedge polygon mapping [33][34][35], and recently in detecting RTS [29]. Broadly, deep learning neural networks have been successfully demonstrated in image classification, segmentation, and object detection, leading to substantial application in remote sensing [36][37][38][39][40][41], coastal erosion [42][43][44][45], and geomorphology [46][47][48].…”
Section: Introductionmentioning
confidence: 99%